Perioperative management of patient with alkaptonuria and associated multiple comorbidities - Ravindra Pandey; Anil Kumar; Rakesh Garg; Puneet Khanna; Vanlal Darlong (Wolters Kluwer Medknow Publications, 2011)
Alkaptonuria is a rare inherited genetic disorder of tyrosine metabolism characterized by a triad of homogentisic aciduria, ochronosis, and arthritis. The most common clinical manifestations of ochronosis involve the musculoskeletal, respiratory, airway, cardiovascular, genitourinary, cutaneous, and ocular systems. We report the perioperative anesthetic management of a 56-year-old alkaptonuric patient, with multiple comorbidities scheduled, for revision total hip replacement. A review of her medical history revealed alkaptonuria, hypothyroidism, rheumatoid arthritis, hypertension, diabetes mellitus, and Pott's spine with disc prolapse. We want to highlight the need of thorough preoperative evaluation in patients of alkaptonuria, as it is associated with multiple comorbidities. The systemic involvement should determine the anesthetic plan. Caution should be exercised during positioning to prevent injury to the joints and the spine.